The child's own story : life story work with traumatized children - Rose, Richard, 1953- (Delivering recovery., 2005)
Helping traumatized children develop a narrative about their life and the lives of people closest to them, is key to their understanding and acceptance of who they are and their past experiences. The Child's Own Story is an introduction to life story work and how this effective tool can be used to help children and young people recover from abuse and make sense of a disrupted upbringing in multiple homes or families. Explaining the concepts of attachment, separation, loss and identity, the authors use these as a context to describe how to use techniques such as family trees, wallpaper work, ec.